ADAPTIVE LEARNING TECHNOLOGIES: PERSONALIZING INSTRUCTION TO ENHANCE STUDENT MOTIVATION AND LEARNING OUTCOMES A LITERATURE REVIEW - Fitriany; Agustin Nurya Savitri; Darry Christine Silowaty Purba (Adisam Publisher, 2026)
The development of digital technology has encouraged the emergence of adaptive learning technologies that allow personalized learning based on students' abilities and needs. This study aims to examine the development of adaptive learning technology and its implications on learning motivation and student learning outcomes through the library research method. Research data was obtained from various reputable scientific articles indexed by Scopus and other relevant academic sources, then analyzed using content analysis techniques to identify research trends, key findings, and research gaps related to adaptive learning. The results of the study show that adaptive learning technology has the potential to increase student engagement and learning motivation through the presentation of materials that are tailored to individual abilities. In addition, personalization of learning also contributes to improved learning outcomes when supported by appropriate pedagogic design and effective technology integration. However, the implementation of adaptive systems still faces challenges related to infrastructure readiness, educator competence, and user data protection aspects. Therefore, future development of adaptive learning will need to integrate technology, pedagogical strategies, and institutional support to create a more effective and sustainable learning experience.